Near and far from our working families. The literature-bomb of Édouard Louis - Martínez Fernández, Ángela (Tropelías: Review of Literary Theory and Comparative Literature, 2025)
This article aims to open a gateway to the study of the French author Édouard Louis that moves away from the most reductionist and frequent visions and places it at the center of a recent event: the frustrated dialogue between sons and daughters who come from working-class backgrounds and gain access, unlike their families, to the audible place, that is, to the public space of enunciation. And from that space, they speak about the subaltern fathers and mothers, but they do so in tension, fricting with themselves. To this end, we will select three axes that place social class and access to public discourse at the center: the uncomfortable condition of their working-class authorship, the relationship with the habitus clivé and the political proposal they raise to articulate a literature-bomb.
Keywords: Édouard Louis; working-class authorship; habitus clivé; literature-bomb; social class